Kelayakan Usaha Diversifikasi Olahan Carica di UD Podang Mas Kabupaten Wonosobo - Mandamdari, Alpha Nadeira; Astuti, Santi Dwi; Novitasari, Dian; Furqon, Furqon; Noorhidayah, Ratri; Widiyawati, Ida (Universitas Galuh, 2025)
In order to enhance its competitive position, UD Podang Mas is not solely concentrating on the manufacture of traditional carica preparations, such as cocktails. Instead, it is also diversifying its product range. This diversification includes the development of new products, such as premium cocktails, jams, concentrates, ready-to-drink beverages, and functional powders derived from carica seeds. The development of these product variants is undertaken in order to meet the increasingly diverse market requirements and changing consumer preferences. In light of the aforementioned description, the objectives of this study can be defined as follows: (1) The objective of this study is to analyze the feasibility of a diversified processed carica business at UD Podang Mas Wonosobo Regency based on non-financial aspects, including market and marketing, management and legal, technical, and social and environmental factors. (2) The second objective is to analyze the feasibility of a diversified processed carica business at UD Podang Mas Wonosobo Regency based on financial aspects. The analysis method used in this research consists of a non-financial analysis and a financial analysis. The non-financial aspects include market aspects, technical aspects, management and legal aspects, as well as social and environmental aspects, which are processed descriptively. In contrast, the financial aspect is quantitative data, which includes the assessment of NPV, Net B/C, IRR, and payback period. The results of the non-financial feasibility analysis at UD Podang Mas indicate that the production of processed carica products is a viable undertaking. This conclusion is supported by findings across a range of relevant domains, including market aspects, technical aspects, management and legal aspects, and social and environmental aspects. A financial analysis of six processed carica products produced by UD Podang Mas suggests that these products are economically viable.